An Unusual Strong Visible‐Light Absorption Band in Red Anatase TiO2 Photocatalyst Induced by Atomic Hydrogen‐Occupied Oxygen Vacancies. Issue 6 (8th January 2018) - Yang, Yongqiang; Yin, Li‐Chang; Gong, Yue; Niu, Ping; Wang, Jian‐Qiang; Gu, Lin; Chen, Xingqiu; Liu, Gang; Wang, Lianzhou; Cheng, Hui‐Ming
Abstract: Increasing visible light absorption of classic wide‐bandgap photocatalysts like TiO2 has long been pursued in order to promote solar energy conversion. Modulating the composition and/or stoichiometry of these photocatalysts is essential to narrow their bandgap for a strong visible‐light absorption band. However, the bands obtained so far normally suffer from a low absorbance and/or narrow range. Herein, in contrast to the common tail‐like absorption band in hydrogen‐free oxygen‐deficient TiO2, an unusual strong absorption band spanning the full spectrum of visible light is achieved in anatase TiO2 by intentionally introducing atomic hydrogen‐mediated oxygen vacancies. Combining experimental characterizations with theoretical calculations reveals the excitation of a new subvalence band associated with atomic hydrogen filled oxygen vacancies as the origin of such band, which subsequently leads to active photo‐electrochemical water oxidation under visible light. These findings could provide a powerful way of tailoring wide‐bandgap semiconductors to fully capture solar light. Abstract : In contrast to the common tail‐like absorption band in hydrogen‐free oxygen‐deficient TiO2, an unusual strong absorption band spanning the full spectrum of visible light is achieved in red anatase TiO2 by intentionally introducing atomic hydrogen‐mediated oxygen vacancies that subsequently lead to active photo‐electrochemical water oxidation under visible light.